If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 6 = 2x + 9 Reorder the terms: 5(-2 + x) + 6 = 2x + 9 (-2 * 5 + x * 5) + 6 = 2x + 9 (-10 + 5x) + 6 = 2x + 9 Reorder the terms: -10 + 6 + 5x = 2x + 9 Combine like terms: -10 + 6 = -4 -4 + 5x = 2x + 9 Reorder the terms: -4 + 5x = 9 + 2x Solving -4 + 5x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 5x + -2x = 9 + 2x + -2x Combine like terms: 5x + -2x = 3x -4 + 3x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 3x = 9 + 0 -4 + 3x = 9 Add '4' to each side of the equation. -4 + 4 + 3x = 9 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 9 + 4 3x = 9 + 4 Combine like terms: 9 + 4 = 13 3x = 13 Divide each side by '3'. x = 4.333333333 Simplifying x = 4.333333333
| 5424=x | | 0,2*5y-2=0,3*(2y-1)-0,9 | | 2(x-1)-4(x+6)=3x-20 | | 5,6-7(0,8x+1)=14-5,32x | | 4x^3=32x^2+36 | | 5x-2x+4=3+7x-12 | | 20x^2=63 | | 0.5=4.1x-2(1.3x+4) | | 4x^3-22x+5=32x^2+14x+5 | | (42+x)=100 | | x+3=2(x-6)+7 | | (100+x)=42 | | 4x^2+32x^2=36 | | 9x^2-3x-13=-7 | | -9y-12=10y-6 | | 36x^2=121 | | 2x-3(x+5)+6=2x+21 | | 225x^2=17 | | xy-6x=0 | | 3(6m-2)-8=9 | | 12x^2=2352 | | (2+15)=2x | | 2(x-7)+3+7=x+9 | | 3x*2=12 | | 9x+1=(7x-2)+(3x+7) | | 7x^2=2268 | | 44.13+.10x=80 | | 8(z+69)=48(z+4) | | 15x^2=4335 | | 38.86+0.50x=130 | | -2=0.25a-13 | | 3(x-5)-2(x+1)=15 |